Audit Delay: Case Studies at Conventional Banking in Indonesia - Wijayanti, Yashinta Putri; Machmuddah, Zaky; Utomo, Stephanus Dwiarso (Faculty of Economics and Business, University of Muhammadiyah Malang, 2019)
The purpose of this study is to determine the effect of company size and profitability on audit delay with the reputation of the public accounting firm as a moderator. The study was conducted at conventional commercial banks in Indonesia during the 2014-2016 period. The total sample was 34 companies with 102 observations. The sample technique used was purposive sampling the analysis in this study used partial least square with WrapPLS. The results showed that company size and profitability has a significant effect on audit delay. The reputation of public accounting firms did not moderate the company size and profitability on audit delay.